The Efficacy of Isochronic Tones via Mobile Application on Sleep Quality of Early Adulthood - Tieocharoen, Peravas; Tangwongchai, Sookjaroen (Journal of Dhamma for Life, 2025)
This research aimed to study the efficacy of Isochronic Tones via mobile application on sleep quality of early adulthood. Data were collected from 70 participants aged 25-45 years who met the inclusion criteria based on physiological and psychological screening tools, including a personal information questionnaire, the SPST-20, HADS, and the Thai version of the STOP-Bang questionnaire. Participants were randomly assigned to an experimental group and a control group using simple random sampling, with 35 participants in each group. The experimental group received Isochronic Tones through a researcher-designed smartphone application for 40 minutes each night before their usual bedtime, over a period of two consecutive weeks, while the control group received no intervention. Data were collected using the Thai version of the Pittsburgh Sleep Quality Index (PSQI), before and after the intervention. The results showed that the experimental group had significantly improved sleep quality, according to PSQI score, after the intervention compared to the pre-intervention scores (p < .001). Furthermore, post-intervention comparisons between the two groups indicated that the experimental group had significantly improved sleep quality score than the control group (p < .001). Specifically, significant improvements were observed in PSQI components 1, 2, and 3: Subjective Sleep Quality, Sleep Latency, and Sleep Duration. These findings suggest that Isochronic Tones auditory stimulation delivered via a smartphone application is effective in enhancing sleep quality in early adulthood individuals and may serve as a safe and accessible alternative tool for addressing sleep problems in this population.